Co-Designing Psychosocial Disability Inclusion: Public Service Innovation in Community-Based Rehabilitation in Yogyakarta, Indonesia - Utami Dewi; Muhamad Nur Chozin; Titis Dewi Anggalini (Department of Public Administration, 2026)
Despite rights-based mental health reforms, persons with psychosocial disabilities continue to experience stigma and exclusion, exposing gaps in the participatory implementation of Community Based Rehabilitation (CBR). Evidence on co-design as a form of governance innovation within CBR remains limited, particularly in decentralized contexts. This study examines how co-design reshapes service delivery, governance arrangements, and social inclusion in CBR initiatives in Yogyakarta, Indonesia. Using a qualitative case study informed by Participatory Action Research, the study draws on interviews, focus groups, participant observation, and policy analysis involving village governments, NGOs, Self-Help Groups (SHGs), and persons with psychosocial disabilities. The findings show that co-design enabled SHG members to shape livelihood activities, enhance agency and recovery, and participate in local decision-making, while generating governance innovations through village regulations, budget allocations, and cross-sectoral collaboration. These practices were constrained by power asymmetries, stigma, and dependence on NGO facilitation. This study conceptualizes co-design as a politically embedded governance process that reconfigures power and participation, underscoring the need for stronger policy alignment to institutionalize inclusive, community-driven rehabilitation.